A Modified Two-Stage Assay Method for Tissue-Thromboplastin (TPLN) - Kale, N. R (Thrombosis and Haemostasis, 1966)
A two-stage method employing purified clotting factors for the assay of tissue-TPLN is described in detail. The rate of prothrombin activation is determined in the presence of optimum amounts of factors V, VII, X and Ca++. The activation of prothrombin is arrested by addition of EDTA or STI, and the thrombin formed is assayed by the clotting method. The method is rapid, sensitive, reproducible and can differentiate between the tissue-TPLN activity of intact lipo-protein and the procoagulant activity of the phospholipids.